Analysis of The Impact of Mobile Application Usage Among Women MSMEs in The Bodetabek (Bogor, Depok, Tangerang,Bekasi) Region on 4 SDGs - Deviana Deviana (Eduvest - Journal of Universal Studies, 2025)
The purpose of this research is to study the readiness, user experience, and difficulties faced by women MSMEs in the BODETABEK area when using e-learning mobile applications related to financial literacy. In addition, this study examines the collaborative approach among stakeholders to provide sustainable mentoring, increase app usage, and the role played by companies and government in supporting financial literacy through mobile apps. The results of the analysis show that most women working in MSMEs are still not proficient in using financial apps, proving that e-learning on financial literacy only provides knowledge and has not been widely used in their business environment. Lack of understanding is the main problem faced, which requires regular monitoring and evaluation. The current focus of the collaboration is on the business aspect and growth of the company rather than ongoing mentoring. In addition, the role of companies and government in using mobile apps as a financial literacy education effort is limited to strategic business objectives and the development of SMEs into companies. The study also found that, while the implementation of mobile apps for financial literacy is still limited, the use of such apps is linked to the objectives of 4 Quality Education, 5 Gender Equality, 8 Sustainable Economic Development, and 17 Partnerships for the Goals.